First record of the genus Scaptesyle Walker (Lepidoptera, Erebidae, Arctiinae, Lithosiini) from mainland China with description of a new species from Xizang - Xu, Yong-Qiang; Volynkin, Anton V.; Huang, Si-Yao (Zootaxa, 2024)
The genus Scaptesyle Walker, 1854 is recorded from mainland China for the first time, with a new species, S. sinotricolor Huang & Volynkin sp. nov. described from SE Xizang Autonomous Region. The comparison is made with S. tricolor Walker, 1854 and S. plumosus Rothschild, 1912. The lectotype has been designated for Scaptesyle tricolor Walker, 1854. The adults and genitalia of the aforementioned species are illustrated.